REVISITING PHILOSOPHICAL FOUNDATIONS OFUNCERTAINTY IN CLASSICAL PHYSICS - V. A. Grechanova; S. N. Pochebut (Дискурс, 2019)
The article addresses the problem of uncertainty in classical thermodynamics and mechanics. The relation of concepts of certainty and uncertainty is studied in detail, and they are considered opposites forming the basis of any system. In addition, a scientific retrospective of this problem is given. It is concluded that both in classical mechanics and thermodynamics the state of uncertainty can be interpreted as a leap in system behaviour, and by it we mean not mechanical motion as a type of physical motion of matter but the change of physical properties within the system quality, i.e. change of its quality. Thus the article confirms that a leap in system behaviour can be considered a transition to a different system quality.